Proteome changes in the small intestinal mucosa of growing pigs with dietary supplementation of non-starch polysaccharide enzymes. Issue 1 (December 2016) - Zhang, Jize; Gao, Yang; Lu, Qingping; Sa, Renna; Zhang, Hongfu
Abstract Background Non-starch polysaccharide enzymes (NSPEs) have long been used in monogastric animal feed production to degrade non-starch polysaccharides (NSPs) to oligosaccharides in order to promote growth performance and gastrointestinal (GI) tract health. However, the precise molecular mechanism of NSPEs in the improvement of the mammalian small intestine remains unknown. Methods In this study, isobaric tags were applied to investigate alterations of the small intestinal mucosa proteome of growing pigs after 50 days of supplementation with 0.6% NSPEs (mixture of xylanase, β-glucanase and cellulose) in the diet. Bioinformatics analysis including gene ontology annotation was performed to determine the differentially expressed proteins. A protein fold-change of ≥ 1.2 and aP -value of < 0.05 were selected as thresholds. Results Dietary supplementation of NSPEs improved the growth performance of growing pigs. Most importantly, a total of 90 proteins were found to be differentially abundant in the small intestinal mucosa between a control group and the NSPE group. Up-regulated proteins were related to nutrient metabolism (energy, lipids, protein and mineral), immunity, redox homeostasis, detoxification and the cell cytoskeleton. Down-regulated proteins were primarily related to transcriptional and translational regulation. Our results indicate that the effect of NSPEs on the increase of nutrient availability in the intestinal lumen facilitates the efficiency of nutrient absorption and utilization, and the supplementation of NSPEs in growing pigs also modulates redox homeostasis and enhances immune response during simulating energy metabolism due to a higher uptake of nutrients in the small intestine. Conclusions These findings have important implications for understanding the mechanisms of NSPEs on the small intestine of pigs, which provides new information for the better utilization of this feed additive in the future.